Expanding access to safe ambulatory manual vacuum aspiration abortion up to 14+6 weeks following Argentina's legal reform: an observational study in the public health sector - Biani Saavedra-Avendano; María Paula Botta; Dolores Chaumet; Berenice Macagno; Guillermo Antonio Ortiz-Avendano (Reproductive Health)
Abstract Background In December 2020, Argentina passed Law 27.610, legalizing elective abortion up to 14 + 6 weeks and beyond in cases of rape or health risks. This study aims to analyze the sociodemographic characteristics of users who opted or were referred for manual vacuum aspiration (MVA) services at an a ambulatory medical center in Argentina before and after the legal reform, and to assess the safety and effectiveness of outpatient MVA procedures for pregnancies up to 14 + 6 weeks. Methods Observational study using clinical data from patients up to 14 + 6 weeks gestation (n = 1,861) who sought or were referred for outpatient MVA abortion at a public healthcare facility in Rosario, Argentina (2017–2023). We analyze changes in users’ sociodemographic characteristics before and after the legal reform and assess the safety and effectiveness of ambulatory MVA abortion by gestational age (< 13 weeks vs. 13–14 weeks). A logistic regression tested associations between sociodemographic, procedural, and reproductive factors, and receiving MVA after 12 weeks. Results Of the 1,861 MVA abortions, 85% (n = 1,590) were provided before 13 weeks’ gestation, and 15% (n = 271) occurred between 13–14 weeks. After the legal reform, more users accessed outpatient MVA services beyond 12 weeks (7% vs. 22%; p < 0.05: before and after the legal change, respectively), including individuals with lower education levels (46% vs. 54%; p < 0.05:), informal employment (34% vs. 47%; p < 0.05), without healthcare insurance (72% vs. 90%; p < 0.05), and nulliparity (18% vs. 30%; p < 0.05). The success rate of ambulatory MVA abortion was 99.9%, with 0.4% (n = 7) adverse events; no statistically significant differences by gestational age groups (< 13 weeks vs. 13–14 weeks). The legal reform was positively associated with accessing MVA abortion after 12 weeks. Conclusions The legal reform improved access to safe ambulatory MVA abortion services up to 14 + 6 weeks’ gestation, particularly for socially disadvantaged users. MVA abortion, both before 13 weeks and at 13–14 weeks, demonstrated a high success rate (99.9%) with minimal adverse events.